Antioxidant potential of atmospheric freeze-dried apples as affected by ultrasound application and sample surface. Issue 8 (11th June 2017) - Moreno, C.; Brines, C.; Mulet, A.; Rosselló, C.; Cárcel, J. A.
ABSTRACT: Atmospheric freeze drying (AFD) yields products of a similar quality to the conventional vacuum freeze-drying technique, but reduces the operating cost. However, it involves very low drying rates. The sample surface/mass ratio is one of the process variables that can be taken into account to reduce drying time. Moreover, power ultrasound (US) can also be used to intensify this process because of its effects on external and internal mass transfer resistance. However, both factors may affect not only the drying time but also the final product quality. Therefore, the aim of this study was to address the influence of both ultrasound application and the sample surface/mass ratio on the drying process and the antioxidant potential of atmospheric freeze-dried apple. For that purpose, two sample geometries with different surface/mass ratio were considered: slabs (30 × 30 × 10 mm 3 ) and cylinders (diameter: 9 mm and height: 30 mm). The samples were freeze dried (−10°C) with ultrasound application (21.7 kHz) at different power levels (0, 10.3, 20.5, and 30.8 kW/m 3 ). The total phenolic content (TPC), antioxidant capacity (AC), and ascorbic acid content (AA) were measured in the dried apple. The drying time was significantly shorter for cylindrical samples than for slabs, probably due to their higher surface/mass ratio. The application of US increased the drying rate, this increase being greater for the slab than for the cylindrical particles used in this study. In general, AFD reduced the TPC, AC, and AA, the final content being significantly greater for slabs than for cylinders. This fact can also be related to the lower surface/mass ratio in the case of slabs. US application further reduced TPC, AC, and AA content, probably due to some cellular damage produced by the acoustic waves and to the oxygen transfer improvement. Nevertheless, the bigger particles (slabs) dried with ultrasound needed a 10% of drying time than the smaller ones (cylinders) dried without ultrasound. Moreover both kind of samples presented similar antioxidant potential.